Mutual Fund Trading Costs and Diseconomies of Scale - Busse, Jeffrey (Institutional Knowledge at Singapore Management University, 2017)
Larger mutual funds underperform smaller funds even though they have lower percentage transaction costs. Larger funds hold and trade a larger fraction of bigger, more liquid stocks, which leads to lower percentage transaction costs than smaller funds. Smaller funds outperform larger funds primarily when small cap stocks outperform large cap stocks. Overall, we find that it is not trading costs but fund holding characteristics, especially the market capitalization of stock holdings, that drive diseconomies of scale in the mutual fund industry.